2005
DOI: 10.1017/s0263034605050512
|View full text |Cite
|
Sign up to set email alerts
|

On Stark broadening as a tool for diagnostics of high density plasmas

Abstract: We present the current status-of-the-art in Stark broadening theory as a theoretical basis for diagnostics of low temperature plasmas in gas discharges, and of high temperature laser produced or z-pinch dense plasmas. The diagnostics abilities vary depending on the parameters of the gas discharges, or on the range of intensity, and duration of the laser or z-pinch pulses. In the case of high temperature plasmas, besides the conventional diagnostics based on the Stark broadening, the contemporary possibilities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…As density increases, the perturbations become stronger, and the spectral line shape broadens in a complex way, making detailed lineshape modeling a challenging enterprise. Nevertheless, the line shape remains a powerful and precise tool to diagnose laboratory and astrophysical plasmas [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…As density increases, the perturbations become stronger, and the spectral line shape broadens in a complex way, making detailed lineshape modeling a challenging enterprise. Nevertheless, the line shape remains a powerful and precise tool to diagnose laboratory and astrophysical plasmas [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that beside the covered in this review problems, there are also many other interesting ones (see recent reviews [195][196][197][198]) or other connected with microfield notion, regrettably not touched here. For example, these are an idea of "mean ion" [158], the so-called NNN distribution [161], the distribution of microfields due to third particle, peculiarities of microfield distributions in dusty plasmas [163], and so on.…”
Section: Discussionmentioning
confidence: 99%
“…This work presents the review of current ideas about plasma microfields, physical models, and methods for describing the quasistatic instantaneous distribution functions and temporary microfield evolution. The most ample previous reviews of this problem could be found in [1,2,11,[14][15][16][17] and the recently published papers [195][196][197][198].…”
Section: Microfield Notionmentioning
confidence: 99%
“…Broadening parameters have been determined theoretically for: Ar ii 476.5 nm, 480.6 nm and Kr ii 469.4 nm lines (Dimitrijević & Csillag 2006), Cd i 33 singlets and 37 triplets (Simić et al 2005a), 26 Ne v multiplets (Hamdi et al 2007) and 15 Si VI multiplets (Hamdi et al 2008). Broadening parameters have been obtained experimentally for: C i 247.8561 nm (Djeniže et al 2006b), Mg ii 448.1 nm (Djeniže et al 2005b), Fe i 381.58 nm (Bengoechea et al 2006) and Fe i 538.34 nm (Bengoechea et al 2005) Stehlé et al (2005) have examined current Stark broadening theory as a basis for diagnostics of low-temperature plasmas and Mahmoudi et al (2008) have provided new expressions for diagonal multiplet factors of complex configurations, required for studies of isolated lines. Zmerli et al (2008) have proposed an improved interpolation method for widths as a function of temperature.…”
Section: Isolated Linesmentioning
confidence: 94%